Optimasi Naive Bayes Menggunakan Particle Swarm Optimization Untuk Meningkatkan Akurasi Deteksi Autisme Spectrum Disorder - Candra Agustina - AMIK BSI Yogyakarta (SPEED - Sentra Penelitian Engineering dan Edukasi, 2018)
Abstract - The number of Autism and Spectrum Autism sufferers in Indonesia is increasing every year. By 2015 an estimated 1 in 250 children have autism, there are 12,800 autistic children or 134,000 people with autism spectrum. Will be able to detect Autistic Spectrum Disorder sufferers today is still difficult and takes a relatively long time. In the world of mental health, to perform their diagnosis on the Diagnostic and Stastistical Manual of Mental Disorder issued by the American Psychiatric Association. Several previous studies have made machine learning for ASD placement based on DSM-5. This study uses datasets from previous research results uploaded in the University of California Irvine machine learning data repository with the title Data Screening Spectrum Autism Spectrum for Adults. The data obtained is then processed using Naïve Bayes and Naïve Bayes algorithms with Particle Swarm Optimization. The data generated as much as 704 data which is then divided into 2 groups of data that is Data Training Total 563 and Data Testing tool 141. The data is then processed with the help of rapidminer software with a model that has been selected previously. From result of data processing result of data processing with naïve bayes yielded data equal to 92,91% and data processing with naïve bayes using Particle Swarm Optimization Algorithm give value equal to 98,51%.Keyword : Autistic Spectrum Disorder, Naïve Bayes, Particle Swarm Optimization, Optimation Abstrak - Jumlah penderita Autisme dan Spektrum Autis di Indonesia mengalami peningkatan setiap tahun. Pada tahun 2015 diperkirakan 1 dari 250 anak menderita autism, artinya ada 12.800 anak penyandang autisme atau 134.000 penyandang spektrum Autis.  Akan tetapi deteksi penderita Autistic Spectrum Disorder sekarang ini masih sulit untuk dilakukan dan memerlukan waktu yang relative lama. Dalam dunia kesehatan jiwa, untuk melakukan diagnosa mereka mengacu pada Diagnostic and Stastistical Manual of Mental Disorder yang dikeluarkan oleh   American Psychiatric Assosiasi. Beberapa penelitian sebelumnya sudah membuat machine learning untuk mendeteksi ASD berdasarkan DSM-5. Penelitian ini menggunakan dataset dari hasil penelitian sebelumnya yang diunggah di University of California Irvine machine learning data repository dengan judul  Autistic Spectrum Disorder Screening Data for Adult. Data yang didapatkan kemudian diolah menggunakan algoritma Naïve Bayes dan Naïve Bayes dengan Particle Swarm Optimization. Data yang diperoleh sebanyak 704 data yang kemudian dibagi kedalam 2 kelompok data yaitu Data Training  sejumlah 563 dan Data Testing berjumlah 141. Data tersebut kemudian diolah dengan bantuan software rapidminer dengan model yang sudah ditentukan sebelumnya. Dari hasil pengolahan data didapatkan bahwa pengolahan data dengan naïve bayes menghasilkan akurasi sebesar 92,91% dan pengolahan data dengan naïve bayes yang digabungkan dengan Algoritma Particle Swarm Optimization memberikan akurasi sebesar 98,51%.Kata Kunci : Autistic Spectrum Disorder, Naïve Bayes, Particle Swarm Optimization, Optimasi